Proses Sosial sebagai Akar Sublimasi Masyarakat Pedesaan - Budiman Pohan; Wahju Gunawan (SIMULACRA: JURNAL SOSIOLOGI, 2019)
The social process is the main basis in forming cooperation and compromise to provide prospects for the achievement of community needs, especially for isolated villages and difficulty accessing public facilities. So it is important for rural communities to improve their level of social processes to more sophisticated levels of resource management. This study aims to determine the characteristics of social processes as a basis for sublimation of rural. This study uses a qualitative approach. Informants were taken purposively with categories of community members, local elites, and village officials. The results showed that the social processes of the Mekarwangi Village community were associative, such as patron-client, mutual cooperation, savings and loans in cooperatives, and annual celebrations. While the dissociative process is in the form of rumors, frictions of political interests, and difficulties of bureaucratic and technological accessibility. The role of the village government in developing socio-economic infrastructure is still minimal due to administrative and funding constraints. Thus, economic empowerment and infrastructure development programs must be supported by the discretion of the village apparatus and community donations. Therefore, sublimation reorientation needs to be done from the bureaucratic and technocratic aspects, in order to diversify agricultural production and encourage sustainable development.